Diterpenoids from the stem bark of Croton megalocarpoides Friis & M. G. Gilbert. (October 2020) - Langat, Moses K.; Ndunda, Beth M.; Salter, Caitlin; Odusina, Babatope O.; Isyaka, Sani M.; Mas-Claret, Eduard; Onocha, Patricia A.; Midiwo, Jacob O.; Nuzillard, Jean-Marc; Mulholland, Dulcie A.
Graphical abstract: Highlights: Ent-clerodane with a rare bicyclo[5.4.0]undecane skeleton was isolated from stembark of C. megalocarpoides Friis & Gilbert. The ent-clerodane with a rare bicyclo[5.4.0]undecane skeleton was determined using logic for structural determination. Four unreported ent- clerodanes were isolated from the stem bark of Croton megalocarpoides Friis & Gilbert. A 1- trans-p -hydroxycoumaroyl–geranylgerani-1-ol was isolated from the stem bark of Croton megalocarpoides Friis & Gilbert. Three ent-clerodanes were evaluated against the NCI60 panel of human tumour cell lines at 10μM but found to be inactive. Abstract: Five previously undescribed compounds, megalocarpoidolide I (1 ), megalocarpoidolide J (3 ), 12- epi- crotonzambefuran A (4 ), megalocarpoidolide K (5 ), 1- trans-p -hydroxycoumaroyl–geranylgerani-1-ol (6 ) were isolated from the stem bark of Croton megalocarpoides Friis & M. G. Gilbert. The known ent -trachyloban-18-ol, megalocarpoidolide B, megalocarpoidolide C (2 ), megalocarpoidolide H, crotocorylifuran, 7, 8-dehydrocrotocorylifuran, 1, 2-dehydrocrotocorylifuran-2-one, acetyl aleuritolic acid, lupeol, N - trans - p -coumaroyl-3′, 4′-dihydroxyphenylethylamine, dodecyl trans -ferulate and lignoceryl trans -ferulate were also isolated. The structures of the compounds were determined using NMR, IR spectroscopy and HRMS. The structure of compound 1 was determined using Logic for Structural Determination (LSD). Compounds 1, 2 and 3 that were selected for screening based on their ability to add diversity to the NCI small molecule compound collection, were evaluated against the NCI60 panel of human tumour cell lines at 10μM level but found to be inactive.